Flexible signalling strategies by victims mediate post-conflict interactions in bonobos - Heesen, R.; Austry, D.A.; Upton, Z.; Clay, Z. (Philosophical Transactions of the Royal Society B: Biological Sciences, 2022)
Compared to other animals, humans supposedly excel at voluntarily controlling and strategically displaying emotional signals. Yet, new data shows that nonhuman great apes' emotion expressions may also be subject to voluntary control. A key context to further explore this is during post-conflict (PC) periods, where signalling by distressed victims may influence bystander responses, including the offering of consolation. To address this, our study investigates the signalling behaviour of sanctuary-living bonobo victims following aggression and its relation to audience composition and PC interactions. Results show that the production of paedomorphic signals by victims (regardless of age) increased their chances of receiving consolation. In adults, the production of such signals additionally reduced the risk of renewed aggression from opponents. Signal production also increased with audience size, yet strategies differed by age: while immatures reduced signalling in proximity of close-social partners, adults did so especially after receiving consolation. These results suggest that bonobos can flexibly adjust their emotion signalling to influence the outcome of PC events, and that this tendency has a developmental trajectory. Overall, these findings highlight the potential role that flexible emotion communication played in the sociality of our last common ancestor with Pan.
EPrint Processing Status: Full text deposited in DRO